Locating Suitable Zones for Beekeeping in Selangor Malaysia. - Mohd Noor, Nisfariza Maris (2007)
Modern beekeeping has been established in Malaysia since 1981 under the collaborative research and development of the Malaysian Beekeeping Research and Development Team (MBDRT), which was funded by International Dutch Research Council (IDRC). During MBDRT research several findings on the of beekeeping implementation in Malaysia have been compiled such as the list of bee plants, prospect ability of the industry and modernisation of beekeeping techniques. Although type of bee plant that supply nectar and pollen which are favourable to honeybees has been identified, the location of the source has not been identified yet and there is no map for suitable beekeeping location or zones especially using GIS and multi-criteria decision analysis technique. This research demonstrates the application of Geographical Information System (GIS) and Multi-Criteria Decision Analysis (MCDA) technology as a tool to aid decision-making process with particular case study of locating a beekeeping zone in the state of Selangor. In this research land suitability analysis is carried out with respect to the bee’s biotic needs and some other important factors in apiary management. The results of the two techniques for AHP with GIS analysis namely refereed VBA Macro in ArcGIS and prominent Weighted Overlay function are presented, compared and discussed with verification of ground truth data. The integration of AHP model with GIS provides zones of Non-Suitable, Most Suitable, Moderately Suitable and Suitable areas for beekeeping activity in Selangor. The total of Non Suitable Area (NS) is 34.73%, leaving the balance of potential areas of 65.27%. The remaining are the Most Suitable Area (S1) 13.72 %, Suitable Area (S2) of 27.24% and Moderately Suitable Area of 24.32 %.